Floral reward traits change between sexual phases in two Helleborus species - Aneta Sulborska-Różycka; Bożena Denisow; Monika Strzałkowska-Abramek; Katarzyna Jaśkiewicz (Scientific Reports)
Abstract Nectar and pollen attractants as well as visitors in Helleborus viridis ssp. viridis and H. purpurascens (Ranunculaceae), i.e. European species, were studied during two flowering seasons. The long-lived flowers of these species are characterized by long nectar availability lasting 15–17 days, i.e. until the end of pollen presentation. On average, approx. 2-fold more nectar and sugar mass was available in the flowers of H. viridis ssp. viridis compared to H. purpurascens. Both species are protogynous, having an initial female phase lasting for 3 days. The nectar and sugar mass was consistently male-biased. At the end of the flower’s life span, the nectar mass and the sugar concentration decreased considerably. In both species, sucrose predominated in the nectar, which also contained small quantities of other disaccharides (maltose and trehalose) and monosaccharides (glucose and fructose). The chemical composition of the nectar sugar varied between the sexual phases; sucrose in the female-phase nectar was replaced mainly by fructose. In addition to nectar, the flowers offered pollen (between 2 and 4 and 10–17 days of anthesis). In the study area, both Helleborus species were foraged by queens of bumble bees and honey bees; however, their distribution differed between the species. Bumble bees dominated in H. viridis subsp. viridis, whereas both pollinator groups were noted with a similar frequency in H. purpurascens.